2020
DOI: 10.1155/2020/6934691
|View full text |Cite
|
Sign up to set email alerts
|

Pore Structure Fractal Characterization and Permeability Simulation of Natural Gas Hydrate Reservoir Based on CT Images

Abstract: The gas-water two-phase seepage process is complex during the depressurization process of natural gas hydrate in a clayey silt reservoir in the South China Sea, the transport mechanism of which has not been clarified as it is affected by the pore structure. In this study, we select six clayey silt samples formed after the dissociation of natural gas hydrate in the South China Sea, employing CT scanning technology to observe the pore structure of clayey silt porous media directly. The original CT scanning image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…In these models, the yellow area represents the sand, while the gray area represents the hydrate. In addition, it could be found that the radius of hydrate particles in pore space would increase gradually as the hydrate saturation increases, and some hydrate particles that do not contact with the sand particles (pore-filling type) will gradually contact with the sand particles (load-bearing type), which is consistent with previous studies [28,29]. Specifically, hydrate saturation calculation was as follows:…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…In these models, the yellow area represents the sand, while the gray area represents the hydrate. In addition, it could be found that the radius of hydrate particles in pore space would increase gradually as the hydrate saturation increases, and some hydrate particles that do not contact with the sand particles (pore-filling type) will gradually contact with the sand particles (load-bearing type), which is consistent with previous studies [28,29]. Specifically, hydrate saturation calculation was as follows:…”
Section: Methodssupporting
confidence: 86%
“…Characteristic Evolution of Pore Space. The pore space could impact the reservoir capacity significantly [29,30], and the PNM is an effective tool to evaluate pore space evolution. In this study, PNM was utilized to estimate the pore and throat characteristics in the porous media under different particle sizes.…”
Section: Resultsmentioning
confidence: 99%
“…CT technology distinguishes materials by their different electron densities and attenuation coefficients [107]. The CT images the habits of hydrate pore with a resolution of tens of microns to sub microns in Figure 8a,b [103,107,108,[110][111][112]. The scanning time is inversely proportional to the resolution and can reach dozens of hours at a resolution of 1 micron [107,108,110].…”
Section: Comparison Of Nmr T 2 Methods With Other Technologiesmentioning
confidence: 99%
“…According to the 3D image, the distributions of the pore size and saturation can be calculated. The permeability can be predicted using Lattice Boltzmann modeling, pore network model, or other predictive permeability models [103,110,117]. However, in CT measurement, the attenuation coefficients of methane hydrates and water (due to their minuscule density difference) are too close to identify methane hydrate segmentation.…”
Section: Comparison Of Nmr T 2 Methods With Other Technologiesmentioning
confidence: 99%
See 1 more Smart Citation